2017
DOI: 10.12738/sm.2017.1.0030
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration among Physicians and Nurses in Intensive Care Units: A Qualitative Study

Abstract: A health care transition project is currently underway in Turkey with the purpose of improving health care access, quality, and continuity of care by increasing patients' and health care professionals' satisfaction and cost effectiveness. Consequently, inter-professional collaboration in providing health care has a crucial role in increasing healthcare access, quality, and continuity of care in Turkey. This study aims to determine the factors influencing the collaborative experiences of nurses and physicians a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The findings seem to be pointing to the existence of a significant negative correlation between patient death rates and physician-nurse collaboration, 10 as well as, a positive correlation between effective physician-nurse collaborative relationships and positive patient outcomes. 11 Studies have reported that poor physician–nurse cooperation could result in job dissatisfaction, a lack of autonomy, and higher possibility of intention to leave the job and poor health. 12,13…”
Section: Introductionmentioning
confidence: 99%
“…The findings seem to be pointing to the existence of a significant negative correlation between patient death rates and physician-nurse collaboration, 10 as well as, a positive correlation between effective physician-nurse collaborative relationships and positive patient outcomes. 11 Studies have reported that poor physician–nurse cooperation could result in job dissatisfaction, a lack of autonomy, and higher possibility of intention to leave the job and poor health. 12,13…”
Section: Introductionmentioning
confidence: 99%
“…Akbal Ergun et al to determine physician-nurse cooperation, it was determined that the professional cooperation between these 2 groups is weak. 20 In our study, the strengthening of the collaborative understanding between physicians and nurses, 2 important members of the health care team, with the HFS method is considered as a remarkable finding. In another study conducted with medical and nursing students, students stated that simulation is valuable in understanding team roles and that working together should be continuous for all nursing and medical students.…”
Section: Discussionmentioning
confidence: 77%